Ovarian cancer in BRCA1/2 mutation carriers: The impact of mutation position and family history on the cancer risk. Issue 2 (October 2015) - Teixeira, Natalia; Mourits, Marian J.E.; Vos, Janet R.; Kolk, Dorina M.van der; Jansen, Liesbeth; Oosterwijk, Jan C.; Bock, Geertruida H.de
Highlights The impact of mutation position and family history on ovarian cancer (OC) risks was assessed. In BRCA1 families women with a mutation within the OCCR region have higher OC risks. In BRCA2 families, mutation position did not significantly affect the OC risk. In BRCA2 families, a family history including only OC presented a strong impact on OC risk.